That was clever of you! Perspectives and verbal irony - Pfeifer Valeria A.; Mehl Matthias R.; Lai Vicky Tzuyin (Psychology of Language and Communication)
What does ironic language indicate about an emotional state? When we experience negative events, we may produce an ironic comment about our experience to cope. We tested whether using irony indexes less negative emotional states of speakers and listeners compared to literal statements. In addition, we tested whether comments directed at the self (“How clumsy/careful of me!”) lead to a different emotional state compared to statements directed at someone else (“How clumsy/careful of you!”). We found that listeners were rated as feeling more negative and more aroused when a statement was directed at them, whereas for speakers, direction did not matter. Further, self-irony led to lower ratings of negativity in speakers. Our results show that whether or not someone is an addressee of a statement matters for their perceived emotional state, and that self-irony may index down-regulated emotional states.